HUBUNGAN RIWAYAT TRAUMA PSIKOLOGIS DENGAN KEJADIAN ISOLASI SOSIAL PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT KHUSUS JIWA SOEPRAPTO PROVINSI BENGKULU - Ade Herman Surya Direja (Jurnal Penelitian, 2020)
Schizophrenia is disorders associated with psychosis consisting of a group of clinical syndromes that are expressed with abnormalities in the contents of thought organizations, interpretation of sensory input, affective / emotional tension, will identity, psychomotor behavior, and the ability to establish satisfying interpersonal relationships. The purpose of this study was to study the relationship between the history of psychological trauma and the incidence of social isolation in schizophrenic patients at Soeprapto Mental Hospital in Bengkulu Province. This type of research is observational analytic using correlational design and using total sampling techniques with inclusion and exclusion criteria for 40 respondents. The population of this study was in schizophrenia patients at Soeprapto Mental Hospital, Bengkulu Province. Date collection techniques with primary and Secondary. Results: From 40 people there were 9 people (22.5%) had a history of psychological trauma, 31 people (77.5%) had no history of psychological trauma, from 40 people there were 16 people (40.0%) social isolation and 24 people (60.0%) did not have social isolation, there was a history of psychological trauma and the incidence of social isolation in schizophrenic patients at the Soeprapto Mental Hospital in Bengkulu Province. It is hoped that the Soeprapto Mental Hospital of Bengkulu Province can provide appropriate treatment and education by using poster and leaflet media when the patient's family is undergoing treatment and increasing the coaching program for schizophrenia patients so social isolation does not occur.